Item Analysis of the Minimum Competency Assessment in Science Subjects at the Junior High School Level - Durriyatus Salsabila (Jurnal Pijar MIPA, 2026)
Minimum Competency Assessment (MCA), known in Indonesia as Asesmen Kompetensi Minimum (AKM), is a national assessment of basic mastery that students must complete. Teachers must be able to compile MCA questions that accurately measure student knowledge. Well-written questions are crucial for creating high-quality assessments. This study analyzes the quality of MCA items on the topic of linear motion in science education at a junior high school in Surabaya. The study aims to evaluate multiple-choice questions using key psychometric parameters, such as validity, reliability, difficulty index, discrimination index, and distractor efficiency. The questions were created by the author and administered to 15 ninth-grade students on 8 May 2024. The analysis used descriptive quantitative methods, and data processing was performed in Microsoft Excel. The results showed that only 4 of 10 items were valid, and the overall reliability coefficient was low (KR-20 = 0.213). Based on the difficulty index, six items were categorized as moderate, three were difficult, and one was easy. The discrimination index analysis revealed that five items had good to excellent discrimination power, whereas others showed poor discrimination and required revision. Distractor efficiency analysis indicated that several distractors were non-functional, particularly in items with low discrimination indices. These findings imply that although some MCA items are suitable for use, many require improvement to ensure accurate, reliable, and diagnostic measurement of student competencies. The study highlights the importance of item analysis as a basis for improving the design of MCA-based assessments in science education.